Effect of monosodium glutamate on the growth of solanum melongena / Hafwanis Awang ... [et al.] - Awang, Hafwanis; Aziz, Aina Sakinah; R. Azmi, Nik Nur Azwarina; Saad, Nur Sazelin; Zamri, Nur Afiqah Shafrini; Seman- Kamarulzaman, Ahmad-Faris (Universiti Teknologi MARA Cawangan Pahang, 2020)
Solanum melongena is one of the vegetable crops broadly planted and has high demand, especially in Asia. Nowadays, chemical fertilizer was used to fulfill the demand as it function to speed up the plant’s growth. However, prolonged use may create an imbalance of soil nutrients and discourage decomposition in soil microbes. Recently, monosodium glutamate (MSG) which is commonly known as food flavoring was reported to be used as alternative fertilizer due to the high content of nitrogen. However, the MSG used was from wastewater of MSG factory which may have the unknown component. Hence, the aim of this study is to determine the optimum concentration of pure MSG (Ajinomoto) towards the growth of S. melongena and how it affects the pH of the soil. The plants were treated by using 1.5g/L, 2.0g/L, 2.5g/L of MSG three times per week for seven weeks. The growth parameters were the plant’s height, number of leaves and width of leaves. The result suggests that the height for all treatment were significantly higher compared to control. All treatment also shows a significantly higher number of leaves compared to the control group except for those with 1.5 g/L treatment. However, no significant difference in leaf width observed from all treatments compared to control. There are no significant changes in soil pH when MSG was used in this study. Hence, the study showed that MSG gives a significant positive effect on S. melongena and can be used as an alternative fertilizer to reduce the usage of chemical fertilizer.